Effects of glycerol monolaurate on growth and physiology of chicks consuming diet containing fumonisin - Fortuoso B.F.* (2020)
© 2020 Elsevier LtdGlycerol monolaurate (GML) is composed of lauric acid and glycerol. Research has shown that such organic acids can minimize negative effects caused by mycotoxins. Therefore, the objective of this study was to determine whether adding GML (free or encapsulated) to chick feed minimizes the effects of natural contamination by fumonisin (Fusarium verticillioides), evaluating parameters such as biochemistry, antioxidant properties, histological analysis and chick growth. Were weighed 84 chicks of the Cobb 500 strain and randomly distributed them into six groups of two replicates each (n = 14). The F group consumed feed containing fumonisin (levels 400 ppb), with no performance enhancer; F + ZB- feed with fumonisin (levels 400 ppb) + zinc bacitracin; F + GLM100 - feed with fumonisin (levels 400 ppb) + 100 mg of GML/kg of feed; F + NGLM4 - feed with fumonisin (levels 400 ppb) + 4 mg GML/kg in nanocapsules added to the feed; F + NGLM8 - fumonisin feed (levels 400 ppb) + 8 mg GML/kg in nanocapsules in the feed; and F0 - fumonisin-free feed (negative control) + zinc bacitracin. The body weights of birds fed with feed fumonisin-contaminated feed (F, F + ZB, F + GLM100, F + NGLM4 and F + NGLM8) were significantly lower (P < 0.05) than those of the negative control (F0), despite the use of GML (free and nanoencapsulated). Serum levels of triglycerides, globulins and cholesterol were significantly lower in the F0 group than in the other groups (P < 0.05), except for the F + NGLM8 group. Significantly greater levels of lipid peroxidation were observed in livers in the groups that consumed fumonisin than in the control group (F0) (P < 0.05). Serum levels of reactive oxygen species were significantly lower in groups F + NGLM8 and F0 than in the other treatments (P < 0.05). Superoxide dismutase activity was significantly greater in groups F + NGLM8 and F0 than in groups F, F + ZB and F + NGLM4. Hepatic catalase activity was significantly lower in birds that consumed contaminated feed (F, F + ZB, F + GLM100, F + NGLM4 and F + NGLM8) than in the control group (F0). Greater hepatic glutathione S-transferase activity was observed in the F + NGLM8 group than in the F0 group. Despite changes in cellular lesions in the liver, no histological changes were observed in the liver or intestines, even though visually there was yellowing of the liver. Taken together, the data suggest that free or nano-encapsulated GML did not minimize oxidative stress caused by fumonisin, and consequently, these birds had less weight gain.